Schools as fearmongering factories: the case of Ahmed Mohamed - Giroux, Henry A. (Revista Hipótese, 2015)
In this essay, it is analyzed the recent case of Ahmed Mohamed, a 14-year-old Muslim high school 9th grader who was questioned by school administrators and the police for bringing a homemade digital clock to school that he had made himself. It is argued that the educational system is broken, reduced largely to a punishing factory defined by a culture of fear and an utter distrust of young people.